Identifikasi Morfologi dan DNA Barcoding Drosophila sp. dari Perangkap Nanas Fermentasi - Permata, Melati; Rahman, Bayu (Insight of Biology, 2025)
Drosophila spp. are model insects with high diversity and play an important role in genetic and ecological studies. This study aimed to identify Drosophila species attracted to fermented pineapple bait using morphological and DNA barcoding approaches. Samples were collected from fermented pineapple traps placed at several sites for seven days. Initial identification was based on external morphological characteristics, while species validation was performed using DNA barcoding with the cytochrome oxidase I (COI) gene. The results showed that fermented pineapple traps were effective in capturing multiple Drosophila species, with Drosophila melanogaster being the dominant species, followed by D. simulans, D. ananassae, and D. immigrans. DNA barcoding analysis successfully reduced misclassification errors that occurred in morphological identification. This study emphasizes the importance of integrating morphological and molecular methods to produce accurate insect biodiversity data in tropical ecosystems